Sigmoid volvulus: devolvulación endoscópica - Estapé, Gonzalo; Marabotto, Nelson; Rompani, Omar (Cirugía del Uruguay, 1983)
A case of sigmoid volvulus treated by fiberoptic colonoscopy is presented. The ·authors analyze the differents nonoperative treatment procedures utili• zed at now (ano-rectal intubation, proctosigmoidos· copy and volvulus reduction by colonoscopy), showing the advantages of the procedure utilized in this case. The importance of avoiding an emergen• cy operation which implies 'high mortality risk is pointed out. According to the authors resection is the definitive treatment.